2014
DOI: 10.1117/12.2062085
|View full text |Cite
|
Sign up to set email alerts
|

Specification of x-ray mirrors in terms of system performance: a new twist to an old plot

Abstract: Abstract. In the early 1990s, Church and Takacs pointed out that the specification of surface figure and finish of x-ray mirrors must be based on their performance in the beamline optical system. We demonstrate the limitations of specification, characterization, and performance evaluation based on conventional statistical approaches, including root-mean-square roughness and residual slope variation, evaluated over spatial frequency bandwidths that are system specific, and a more refined description of the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The forecast data are vital for reliable specification for optical fabrication, with evaluation from numerical simulation being necessary and sufficient for the required system performance, avoiding both over-and underspecification. 12,13 In this work, we continue investigations, started in Refs. 8-14; we consider surface slope metrology data sto-chastic and stationary and use a compact volume of metrol-ogy data to develop the TILF model 15 and determine its parameters.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The forecast data are vital for reliable specification for optical fabrication, with evaluation from numerical simulation being necessary and sufficient for the required system performance, avoiding both over-and underspecification. 12,13 In this work, we continue investigations, started in Refs. 8-14; we consider surface slope metrology data sto-chastic and stationary and use a compact volume of metrol-ogy data to develop the TILF model 15 and determine its parameters.…”
Section: Introductionmentioning
confidence: 82%
“…Models of AR type turned out to be most suited for description of the surface slope data measured with high quality x-ray mirrors as surfaces under testing. [8][9][10][11][12][13][14] In our previous work, 10,11 we have described the construc-tion of InTILF models of AR, MA, and ARMA types (sym-metric ARMA models) and determination of its coefficients. We have shown that the optimal InTILF model of a given type (AR, MA, or ARMA) and given number of coefficients can be derived analytically using the ACF of the data.…”
Section: Brief Review Of Statistical Modeling Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The mirror substrates made of single-crystal silicon have overall dimensions of 160 (length) × 50 (width) × 50 (thickness) mm 3 with clear apertures (CA) of 150 mm × 20 mm for SM1 and SM2 mirrors, and 300 × 50 × 75 mm 3 1. The Wolter Type I optical system consisting of a pair of mirrors, one hyperbolic and one elliptical.…”
Section: A Tolerance Specification Of Pre-shaped X-ray Mirrors and Nmentioning
confidence: 99%
“…The development of fully coherent free electron lasers and diffraction limited storage ring x-ray sources has brought to a focus the need for higher performing x-ray optics with unprecedented tolerances for surface slope and height errors and roughness. [1][2][3][4][5] For example, the proposed beamlines for the future upgraded Advanced Light Source, ALS-U, 6,7 require mirrors characterized by a residual slope error of <100 nrad (root-mean-square, RMS) and a height error of <1-2 nm (peakto-valley, PV). Such high quality aspherical x-ray mirrors are now available from a number of the most advanced vendors utilizing deterministic polishing techniques.…”
Section: Introductionmentioning
confidence: 99%